Too Healthy to Fall Sick? Longevity Expectations and Protective Health Behaviours during the First Wave of COVID-19 - Martina Celidoni; Joan Costa-Font; Luca Salmasi (Institute of Labor Economics (IZA), 2022)
Longevity expectations (LE) are subjective assessments of future health status that can influence a number of individual health protective decisions. This is especially true during a pandemic such as COVID-19, as the risk of ill health depends more than ever on such protective decisions. This paper exploits differences in LE to examine the causal effect of LE on protective health behaviours and a number of decisions around access to health care, using data from the Survey of Health Ageing and Retirement in Europe. We draw on an instrumental variable strategy exploiting individual level information on parental age at death. Consistent with the too healthy to be sick hypothesis, we find that individuals with higher expected longevity are more likely to engage in protective behaviours, and are less likely to forgo medical treatment. We estimate that a one standard deviation increase in expected longevity increases the probability to comply always with social distancing by 0.6%, to meet people less often by 0.4% and decreases the probability to forgo any medical treatment by 0.6%. Our estimates vary depending on the availability of health care, as well as individuals' gender and pre-existing health conditions.
Keywords: I12; I18; 330; SHARE; longevity expectations; private information; health behaviours; forgone medical treatment; health capital; Europe; instrumental variables; COVID-19